The cultural, economic and regulatory environment affecting the adoption of marginal quality water and risk reduction measures - Alcon, F.; Drechsel, Pay (2023)
In response to growing water scarcity and pollution in agricultural regions, the discussion focuses on the enabling conditions required for farmers to safely use marginal quality water (MQW) and adopt effective risk mitigation practices. Three key scenarios are considered: the planned use of treated wastewater, informal use of polluted water in the absence of alternatives, and soil salinity management in irrigated areas. Adoption is shaped by a mix of financial incentives, public perceptions, regulatory support, and awareness levels. In Jordan and Tunisia, trust in water reuse has been enhanced through public education and stakeholder engagement, while elsewhere, low awareness and weak institutional backing hinder safer practices. Unlike the invisible risks of contaminated wastewater, salinity is directly observable and often triggers farmer-led responses but still requires coordinated catchment-level strategies. A conceptual framework is introduced to help policymakers and practitioners design locally tailored interventions that account for behavioral, technical, and environmental drivers, advancing safer and more sustainable water use in agriculture.